Water Quality Analysis (Physicochemical) Based on the Pollution Index in Pangempang Waters, Muara Badak, Kutai Kartanegara - Lana, Achmad Rivaldy; Nurfadilah, Nurfadilah; Ritonga, Irwan Ramadhan (Dept. Marine Science, 2026)
The entry of pollutants into the aquatic environment has the potential to degrade water quality, thereby lowering the water quality status and threatening the survival of aquatic biota. This study aimed to determine the water quality status based on physicochemical parameters in the waters of Pangempang, Muara Badak, Kutai Kartanegara. Observations were conducted at six stations, located both inside and outside the bay using a combination of field measurements and laboratory analyses. Physical parameters observed included temperature, transparency, current, and turbidity, while chemical parameters included BOD₅, dissolved oxygen, phosphate, nitrate, pH, and salinity. Water quality assessment utilized the Pollution Index method, referencing the State Minister for the Environment Decree No. 115 of 2003, with marine biota quality standards based on the State Minister for the Environment Decree No. 51 of 2004. The results indicated that certain parameters fell below the quality standards, specifically dissolved oxygen (3.69 mg/L) and phosphate (0.005–0.023 ± 0.011 mg/L), whereas turbidity (24.1 NTU) and nitrate (0.095 mg/L) exceeded the standard thresholds, necessitating monitoring. The calculated Pollution Index value was 3.23, indicating that the waters are classified as lightly polluted.